[Ind2TiMe2]: a general catalyst for the intermolecular hydroamination of alkynes - Heutling, Andreas; Pohlki, Frauke; Doye, Sven (Chemistry - a European journal, 2004)
Abstract: [Ind2TiMe2] (Ind=indenyl) is a highly active and general catalyst for the intermolecular hydroamination of alkynes. It catalyzes the reaction of primary aryl-, tert-alkyl-, sec-alkyl-, and n-alkylamines with internal and terminal alkynes. In the case of unsymmetrically substituted 1-phenyl-2-alkylalkynes, the reactions occur with modest to excellent regioselectivities, whereby formation of the anti-Markovnikov regioisomers is favored. While the major product of hydroamination reactions of terminal arylalkynes is always the anti-Markovnikov isomer, alkylalkynes react with arylamines to preferably give the Markovnikov products. To achieve reasonable rates for the addition of sterically less hindered n-alkyl- and benzylamines to alkynes, these amines must be added slowly to the reaction mixtures. This behavior is explained by the fact that the catalytic cycle proposed on the basis of an initial kinetic investigation includes the possibility that the rate of the reaction increases with decreasing concentration of the employed amine. Furthermore, no dimerization of the catalytically active imido complex is observed in the hydroamination of 1-phenylpropyne with 4-methylaniline in the presence of [Ind2TiMe2] as catalyst. In general, a combination of [Ind2TiMe2]-catalyzed hydroamination of alkynes with subsequent reduction leads to the formation of secondary amines with good to excellent yields. Particularly impressive is that [Ind2TiMe2] makes it possible for the first time to perform the reactions of n-alkyl- and benzylamines with 1-phenylpropyne in a highly regioselective fashion.